Homophily in delinquent behavior: The rise and fall of friend similarity across adolescence. (January 2019) - Richmond, Ashley D.; Laursen, Brett; Stattin, Håkan
This study examined age-related changes in friend similarity on delinquency to determine whether deviant behavior homophily peaks during mid-adolescence. A community sample of 1, 663 male and 1, 826 female Swedish youth from Grade 5 ( M = 11.21 years) to Grade 10 ( M = 16.25 years) provided self-reports of delinquency. Friendships were identified from nominations. Intraclass correlations revealed age group differences in friend delinquency similarity, independent of normative age-related changes in deviant behavior. Cross-sectional results indicated that similarity was greatest in the seventh grade ( M = 13.21 years). Longitudinal results from a subsample of participants revealed an increase in friend similarity from ages 11 to 13 (Grades 5 to 7) and a decline in friend similarity from ages 14 to 16 (Grades 8 to 10). The findings demonstrate that similarity between friends in delinquent behavior peaks in mid-adolescence, independent of normative age-related changes in participation in deviant acts.